ANALISIS PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL, DAN KECERDASAN SPIRITUAL TERHADAP KINERJA MANAJERIAL PADA HOTEL-HOTEL BERBINTANG 3 DI PEKANBARU - Elpista Tarigan; Amries Rusli Tanjung; Edfan Darlis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The number of hotels in Pekanbaru from year to year is always increasing. This shows the increasing competition among entrepreneur of hospitality services. Have a competent leader / manager would be one of the important things that must be considered. This study aims to: examine, test and analyze the effect of intellectual quotient, emotional quotient and spiritual quotient on managerial performance. This study is conducted in 3-star hotels in Pekanbaru. The research sample is 31 people hotel manager. Data collected directly from respondents using research instruments such as questionnaires and data analysis techniques using linear regression analysis with SPSS 18.0. The results of this study prove that the intelligence quotient significant effect on managerial performance, emotional intelligence have a significant effect on the performance of managerial and spiritual intelligence significantly influence managerial performance. The implications of this research are intellectual quotient, emotional quotient and spiritual quotient have an equally important role in improving the performance of a manager.Keywords: Intelectual quotient, emotional quotient, spiritual quotient and managerial performance